Molecular determinant for specificity: differential interaction of alpha-amylases with their proteinaceous inhibitors - Rane, Ashwini S.; Joshi, Rakesh S.; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2020)
Background: alpha-Amylase inhibitors (alpha-AIs) belong to the discrete classes, and exhibited differential specificities against alpha-amylases from various sources. Several alpha-amylases and their complexes with inhibitors at the molecular level have been studied in detail. Interestingly, some alpha-AIs depict specific and selective interactions amid different insect alpha-amylases. Scope of review: There are studies to understand evolutionary variability and functional differentiation of insect alpha-amylases and their cognate inhibitors. We have examined sequence, structural, and interaction diversity between various alpha-amylases and alpha-AIs. Based on these analyses, we are providing a potential basis for the functional differentiation among certain insect a-amylases concerning mammalian counterparts and their interactions with different proteinaceous alpha-AIs. Major conclusions: Insect alpha-amylases have conserved domain architecture with differences in length, number of disulfide bonds, and secondary structure. Furthermore, few of them exhibit variable characteristics like chloride dependent activity, the presence of N-terminal glutamine residue to protect against proteolytic degradation, and loop variations near the enzyme active site. Conformation of alpha-AI protein could be an essential factor for their specificity and binding affinities towards target alpha-amylase(s). Furthermore, variation into the enzyme binding pocket residues might contribute to differential interactions with inhibitors. General significance: Molecular insights in the interactions between insect alpha-amylases and plant alpha-AI will provide the details of mechanisms assisting the inhibitor specificity. Furthermore, this information will help to design potent and effective alpha-AIs against specific alpha-amylase.
Keywords: Active site; alpha-amylase; alpha-amylase inhibitor; Insect; molecular interactions